Enhancing Community Resilience in Facing Landslide Hazards through Education and Mitigation in Pasirmunjul Village, Sukatani District, Purwakarta - Sutarman Sutarman; Lina Sukanti; Herlina; Srimulyeni; Neneng Sulastri (The International Journal of Education Management and Sociology, 2025)
Pasirmunjul Village, located in Sukatani District, Purwakarta Regency, is categorized as a landslide-prone area due to its hilly topography and high rainfall. The limited public understanding of disaster risks and lack of preparedness represent serious challenges in disaster risk reduction. This community engagement initiative aimed to improve local resilience through educational and mitigation-based approaches. The activities included public awareness campaigns, emergency response training, evacuation simulations, and environmental conservation education to help prevent future ground movement. The results showed a significant improvement in residents' understanding of landslide risks, readiness for emergencies, and active participation in protecting the surrounding environment. This program is expected to strengthen the community’s capacity to independently and sustainably anticipate and manage landslide disasters.